High Rate of Hepatitis C Virus Reinfection Among Recently Injecting Drug Users: Results From the TraP Hep C Program—A Prospective Nationwide, Population-Based Study. (19th April 2022) - Johannesson, Jon M; Fridriksdottir, Ragnheidur H; Löve, Thorvardur J; Runarsdottir, Valgerdur; Hansdóttir, Ingunn; Löve, Arthur; Thordardottir, Marianna; Hernandez, Ubaldo B; Olafsson, Sigurdur; Gottfredsson, Magnus; ,
Abstract: Background: The Treatment as Prevention for Hepatitis C program started in 2016 in Iceland, offering treatment with direct-acting antivirals to hepatitis C virus (HCV)-infected individuals. Reinfections through injection drug use (IDU) can hamper elimination efforts. We determined reinfection rates of HCV among patients in the program. Methods: Clinical data were gathered prospectively. The study cohort consisted of HCV-cured patients with an estimated sustained virologic response between 1 February 2016 and 20 November 2018, with follow-up until 20 November 2019. The observation period and time until reinfection was estimated using a single random point imputation method coupled with Monte Carlo simulation. The reinfection rates were expressed as reinfections per 100 person-years (PY). Results: In total, 640 treatments of 614 patients (417 male; mean age, 44.3 years) resulted in cure, with 52 reinfections subsequently confirmed in 50 patients (37 male). Follow-up was 672.1 PY, with a median time to reinfection of 232 days. History of IDU was reported by 523 patients (84.8%) and recent IDU with 220 treatments (34.4%). Stimulants were the preferred injected drug in 85.5% of patients with a history of IDU. The reinfection rate was 7.7/100 PY. Using multivariate Cox proportional hazards models for interval-censored data, age (hazard ratio, 0.96 [95% confidence interval, .94–.99]) and recent IDU (2.91 [1.48–5.76]) were significantly associated with reinfection risk. Conclusions: The reinfection rate is high in a setting of widespread stimulant use, particularly in young people with recent IDU. Regular follow-up is important among high-risk populations to diagnose reinfections early and reduce transmission. Clinical Trials Registration: NCT02647879. Abstract : Rates of reinfection with hepatitis C virus after successful treatment with direct-acting antivirals are high in Iceland, particularly among young individuals with recent injection drug use. Emphasis on further follow-up of high-risk groups is essential.